SISTEM INFORMASI PENJUALAN TIKET PO. METRO EXPRESS - -, Alamsyah (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2011)
Service provider anggkutan common ground (PO), expeditionary passenger land transport executive, in data processing is still done manually. Therefore, when entering and finding data still requires quite a long time. Therefore we need an application system that can simplify and speed up the search or passenger data collection. Ticket Sales Information System Bureau of Land Transport (PO) is a desktop-based applications. This application is created using Visual Basic programming for database processing. Ticket Sales Information System is composed of 3 (three) main menu, the menu is the menu Master, transactions and reports. Menu Master has a submenu that is menu data driver, route fare menu and a menu list of cars. Tansaksi menu consists of 2 (two) sub-menus namely passenger ticket booking and ticket delivery ordering menu. On the menu reports 4 (four) sub-menu that is based on the date of filling the manifest, passenger manifest persopir, perpriode manifestn certain passenger and the passenger manifest month. Report menu is designed to be able to store data to be viewed at any - time and can print the tickets of passengers and passenger manifest. Keywords: Information Systems, Data Base.